Periodontal Disease and its Relationship with Diabetes - Jennifer Dayana Cárdenas Velastegui; Danna Mabel Castro Freire; Leslie Fernanda Dávila Alemán; Oswaldo Miranda Rosero (Revista Finlay)
Diabetes mellitus is a systemic disease currently suffered by a large part of the population. Having a systemic disease predisposes the appearance of periodontal diseases. The severity of periodontal disease is affected by the inflammatory response. Cells such as IL-1β, IL-6, and TNF-α are chronically and persistently elevated. The prevalent periodontal disease in diabetic patients is usually periodontitis due to systemic diseases. Certain affectations are observed in ligaments and bone (deterioration or loss), so it is important that the dentist knows everything that periodontal disease involves in a diabetic patient. For the present investigation, a bibliographic review was carried out in important databases such as: Pubmed and Scopus. The proposed objective was: to establish the relationship between periodontal diseases and diabetes and to determine the periodontal diseases with the highest prevalence in diabetic patients.